Development of innovation methods by the affection at extreme impact on the basis of laser, nuclear and biological technologies; Интеллектуальные энергосистемы; Т. 3 - Borisov V. Y. (Научно-технический дискурс "Интеллектуальные энергосистемы", 2016)
Заглавие с титульного экрана